2007
DOI: 10.1073/pnas.0608807104
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid precursor protein overexpression depresses excitatory transmission through both presynaptic and postsynaptic mechanisms

Abstract: Overexpression of the amyloid precursor protein (APP) in hippocampal neurons leads to elevated ␤-amyloid peptide (A␤) production and consequent depression of excitatory transmission. The precise mechanisms underlying APP-induced synaptic depression are poorly understood. Uncovering these mechanisms could provide insight into how neuronal function is compromised before cell death during the early stages of Alzheimer's disease. Here we verify that APP up-regulation leads to depression of transmission in cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
88
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 30 publications
(34 reference statements)
12
88
1
Order By: Relevance
“…Taken collectively, these data suggested that this deficiency emerges when the level or speed of synaptic vesicle recycling is increased under sustained synaptic activity. In contrast, no decrease in dye uptake was observed when hippocampal neurons overexpressing APP were cultured as microislands (Ting et al, 2007). Possible explanations of this discrepancy are the different age (embryonic vs. postnatal), species (rats vs. mice), and culture conditions (dissociated vs. microisland cultures) used in these two studies.…”
Section: Discussionmentioning
confidence: 38%
See 2 more Smart Citations
“…Taken collectively, these data suggested that this deficiency emerges when the level or speed of synaptic vesicle recycling is increased under sustained synaptic activity. In contrast, no decrease in dye uptake was observed when hippocampal neurons overexpressing APP were cultured as microislands (Ting et al, 2007). Possible explanations of this discrepancy are the different age (embryonic vs. postnatal), species (rats vs. mice), and culture conditions (dissociated vs. microisland cultures) used in these two studies.…”
Section: Discussionmentioning
confidence: 38%
“…Aβ could also induced changes in postsynaptic elements that might contribute to synaptic dysfunction. Thus, it has been recently shown that APP over expression led to a selective reduction of α-amino-3-hydroxy-5methyl-4-isoxazole-propionic acid (AMPA) receptors, and hence, disruption in excitatory transmission in hippocampal neurons (Chang et al, 2006;Ting et al, 2007). However, it is unlikely that these defects are mediated by dynamin 1 depletion since these proteins are localized in different subcellular compartments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Role of cAMP signaling and AC1/AC8 in basal and FSK unsilencing Our own and others' previous results have demonstrated that a fraction of hippocampal presynaptic terminals are silent under basal conditions (Rosenmund et al, 2002;Altrock et al, 2003;Moulder et al, 2006;Ting et al, 2007) (Fig. 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…By a combination of optical and electrophysiological measures, our work shows strong evidence that cAMP signaling activates previously silent presynaptic terminals. We and others have demonstrated previously the existence of presynaptically silent synapses under basal conditions, defined by normal antibody staining for synaptic vesicle markers but lack of FM dye labeling during brief, strong depolarization (Rosenmund et al, 2002;Altrock et al, 2003;Moulder et al, 2006;Ting et al, 2007). There is an important role for cAMP potentiation in the awakening of these basally silent presynaptic terminals.…”
Section: Camp and Presynaptic Potentiationmentioning
confidence: 99%